Worker assessments of organizational practices and psychosocial work environment are associated with musculoskeletal injuries in hospital patient care workers. Issue 7 (15th April 2014) - Reme, Silje Endresen; Shaw, William S.; Boden, Leslie I.; Tveito, Torill H.; O'Day, Elizabeth Tucker; Dennerlein, Jack T.; Sorensen, Glorian
<x xml:space="preserve">Abstract</x> Background Hospital patient care (PC) workers have high rates of workplace injuries, particularly musculoskeletal injuries. Despite a wide spectrum of documented health hazards, little is known about the association between psychosocial factors at work and OSHA‐recordable musculoskeletal injuries. Methods PC‐workers (n = 1, 572, 79%) completed surveys assessing a number of organizational, psychosocial and psychological variables. Associations between the survey responses and injury records were tested using bivariate and multivariate analyses. Results A 5% of the PC‐workers had at least one OSHA‐recordable musculoskeletal injury over the year, and the injuries were significantly associated with: organizational factors (lower people‐oriented culture), psychosocial factors (lower supervisor support), and structural factors (job title: being a patient care assistant). Conclusions The results show support for a multifactorial understanding of musculoskeletal injuries in hospital PC‐workers. An increased focus on the various dimensions associated with injury reports, particularly the organizational and psychosocial factors, could contribute to more efficient interventions and programs. Am. J. Ind. Med. 57:810–818, 2014. © 2014 Wiley Periodicals, Inc.